Dietary glycemic index and glycemic load in association with sleep duration: YaHS-TAMYZ and Shahedieh observational studies. (December 2021) - Mohammadi, Mohammad; Nadjarzadeh, Azadeh; Mirzaei, Masoud; Fallahzadeh, Hossien; Haghighatdoost, Fahimeh; Sakhaei, Roya; Abolhosseini, Hossein; Salehi-Abargouei, Amin
Summary: Background & aims: Current data on the association between dietary glycemic index (GI) and glycemic load (GL) and sleep duration are limited and controversial. The present cross-sectional study aimed to investigate the relationship between dietary GI and GL with sleep duration in a large number of adults living in central Iran. Methods: Baseline data from two Iranian cohorts were pooled for the current analysis: the YaHS-TAMYZ (n = 9962) and Shahedieh (n = 9977) studies. Demographic data as well as dietary intakes, sleep duration, and possible confounders, were collected by interview. Anthropometric measurements were also conducted by trained interviewers. Participants were categorized based on sleep duration [short (<6 h), normal (6–8 h), and long (>8 h)]. Multivariable logistic regression was used to determine the relationship between dietary GI/GL and the likelihood of short and long sleep duration. Results: In total, 10, 451 participants aged 20–70 years were included in the analyses. After controlling for all possible confounders, no significant association was observed between dietary GI and short or long sleep duration (P > 0.05). Individuals in the highest quartile of dietary GL had a higher chance for long sleep duration compared to participants in the lowest quartile (OR = 1.41; 95% CI: 1.14, 1.74, Ptrend  = 0.001). No significant association was observed between dietary GL and short sleep duration. Conclusion: Dietary GL is positively associated with the likelihood of long sleep duration. Future prospective studies are required to confirm the current findings.